Lantana camara alleviating TNBS-induced ulcerative colitis in rats: regulating TNF-α/EGFR/STAT3/Bcl-2 signaling pathways - S. Magre Manoj; A. Bhalerao Pooja; K. Mandlik Satish; S. Mandlik Deepa (Digital Chinese Medicine)
Objective: To investigate the therapeutic potential and underlying mechanism of Lantana camara ethanolic extract (LCEE) in ulcerative colitis (UC). Methods: Phytochemical analysis of LCEE was conducted using qualitative analysis, liquid chromatography-mass spectrometry (LC-MS), and high-performance thin-layer chromatography (HPTLC). The active constituents of LCEE were identified through network pharmacology analysis, followed by molecular docking. The therapeutic mechanism was validated in a UC rat model using 42 male Wistar rats (200 – 250 g) induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS). Rats were randomly divided into seven groups (n = 6 per group): normal control (NC), ethanol control (EC), disease control (DC), three doses of LCEE treatment [low dose LCEE (100 mg/kg), medium dose LCEE (200 mg/kg), and high dose LCEE (400 mg/kg), p.o.], and dexamethasone (DEX, 2 mg/kg, p.o.) groups. Following TNBS-induced UC (120 mg/kg, intrarectally), rats were treated orally for 28 d. Disease severity was assessed through body weight changes, disease activity index (DAI), colon weight, colon length, and morphological scores. Haematological parameters, enzymatic antioxidants, nitric oxide (NO), myeloperoxidase (MPO), and inflammatory cytokines were measured in the serum and colon tissues. Gene expressions of tumor necrosis factor (TNF)-α, epidermal growth factor receptor (EGFR), signal transducer and activator of transcription 3 (STAT3), and B-cell lymphoma 2 (Bcl-2) were analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Histopathological alterations in the colon tissues were evaluated using hematoxylin and eosin (HE), Giemsa, and periodic acid-schiff staining (PAS). Results: LC-MS analysis identified 13 phytoconstituents in LCEE, and HPTLC analysis confirmed the presence of ursolic acid, geniposide, and chlorogenic acid. Network pharmacological analysis identified 152 potential therapeutic targets with TNF, STAT3, Bcl-2, albumin (ALB), and EGFR as the top 5 hub targets. Molecular docking revealed strong binding affinities of LCEE phytoconstituents with key inflammatory and apoptotic targets: linaroside with TNF-α (– 6.1 kcal/mol), ursolic acid with STAT3 (– 6.8 kcal/mol) and Bcl-2 (– 8.7 kcal/mol), and cirsiliol with EGFR (– 8.2 kcal/mol), comparable to DEX. LCEE treatment significantly increased body weights and thymus weight, while significantly reducing colon weight, spleen weight, and DAI scores. Haematological parameters showed significant improvements with increased haemoglobin, red blood cells, and platelet count, and decreased white blood cells counts. Antioxidants markers were significantly improved with increased glutathione, superoxide dismutase, and catalase levels, and decreased malondialdehyde levels. LCEE significantly reduced NO and MPO levels and inflammatory cytokines including TNF-α, interleukin (IL)-1β, nuclear factor kappa-B (NF-κB), IL-6, and IL-12 compared with TNBS treated rats. LCEE downregulated the gene expression levels of TNF-α, EGFR, and STAT3, while upregulating Bcl-2 expression level, indicating modulation of inflammation and apoptosis pathways. Histological evaluation confirmed that after LECC treatment, mucosal ulcers and inflammatory cell infiltration decreased. Conclusion: The findings suggest that Lantana camara may serve as a medicinal plant to alleviate UC and offer an investigational basis for the clinical utilization of Lantana camara.